The use of fluoride dentifrices in children: conceptual bases in a confusing context: a topic review - María Cecilia Martínez-Pabón; David Andrés Galvis-Pareja; Ángela Patricia Builes-Sánchez; Diego Alejandro García-Ortega; Liseth Tatiana Cañas-Londoño; María Isabel Arango-Arango (Universidad de Antioquia, 2017)
Fluoride toothpastes have long been recommended as part of the measures to prevent dental caries. Controversial findings suggest that an inappropriate use of this type of dentifrices can significantly contribute to the total intake of fluoride by children younger than 3 years, being one of the reasons why they have been linked to the development of dental fluorosis. The cost-benefit relationship of using fluoride dentifrices in children has been controversial and has allowed the evolution of concepts that reinforce the recommendations to use them. This topic review discusses some aspects that determine the preventive potential of fluoride toothpastes, the academic recommendations to use them, the various policies in Latin American countries on the issue, and a brief description of the availability of products in the Colombian market. This article seeks to contribute to a better understanding of this issue and therefore to a better orientation of patients.